Cardiovascular outcomes at recommended blood pressure targets in middle-aged and elderly patients with type 2 diabetes mellitus compared to all middle-aged and elderly hypertensive study patients with high cardiovascular risk. (4th March 2021) - Olsen, Eirik; Holzhauer, Björn; Julius, Stevo; Kjeldsen, Sverre E.; Larstorp, Anne Cecilie K.; Mancia, Giuseppe; Mehlum, Maria H.; Mo, Rune; Rostrup, Morten; Søraas, Camilla L.; Zappe, Dion; Weber, Michael A.
Abstract: Purpose: Event-based clinical outcome trials have shown limited evidence to support guidelines recommendations to lower blood pressure (BP) to <130/80 mmHg in middle-aged and elderly hypertensive patients with diabetes mellitus or with general high cardiovascular (CV) risk. We addressed this issue by post-hoc analysing the risk of CV events in patients who participated in the Valsartan Antihypertensive Long-term Use Evaluation (VALUE) trial and compared the hypertensive patients with type 2 diabetes mellitus with all high-risk hypertensive patients. Materials and methods: Patients were divided into 4 groups according to the proportion of on-treatment visits before the occurrence of an event (<25% to ≥75%) in which BP was reduced to <140/90 or <130/80 mmHg. Patients with diabetes mellitus ( n = 5250) were compared with the entire VALUE population with high CV risk ( n = 15, 245). Results: After adjustments for baseline differences between groups, a reduction in the proportion of visits in which BP was reduced to <140/90 mmHg, but not to <130/80 mmHg, was accompanied by a progressive increase in the risk of CV morbidity and mortality as well as stroke, myocardial infarction and heart failure in both diabetes mellitus and in all high-risk patients. Target BP <130/80 mmHg reduced stroke risk in the main population but not in the diabetes mellitus patients. Patients with diabetes mellitus had higher event rates for the primary cardiac endpoint and all-cause mortality driven by a higher rate of heart failure. Conclusion: In the high-risk hypertensive patients of the VALUE trial achieving more frequently BP <140/90 mmHg, but not <130/80 mmHg, showed principally the same protective effect on overall and cause-specific cardiovascular outcomes in patients with diabetes mellitus and in the general high-risk hypertensive population.